Bilateral oculomotor nerve palsy in a case of anti-aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder. (August 2019) - Yasuda, Ken; Maki, Takakuni; Takata, Masaki; Kimura, Kimitoshi; Takahashi, Toshiyuki; Kanbayashi, Takashi; Murase, Nagako; Ohtani, Ryo; Takahashi, Ryosuke; Nakamura, Michikazu
Highlights: NMOSD sometimes shows brainstem manifestations with abnormal eye movement. Bilateral oculomotor nerve palsy with midbrain lesion has never been reported in NMOSD. We report a first case of bilateral oculomotor nerve palsy with NMOSD. Abstract: Neuromyelitis optica spectrum disorder (NMOSD) has a wide disease spectrum and sometimes shows abnormal eye movement with brainstem manifestations. However, bilateral oculomotor nerve palsy with a midbrain lesion has never been reported in a patient with NMOSD. We describe a 61-year-old woman with progressive ptosis and diplopia. She displayed bilateral oculomotor nerve palsy and hypersomnia. Brain MRI demonstrated abnormal signal intensities in the midbrain and around the third ventricle and hypothalamus with a mild contrast enhancement. A cerebrospinal fluid study indicated elevated protein and pleocytosis. Because serum anti-aquaporin-4 IgG antibody was positive, the patient was diagnosed with neuromyelitis optica spectrum disorder with aquaporin-4 IgG. We report for the first time bilateral oculomotor nerve palsy as an initial manifestation in a patient with aquaporin-4 positive NMOSD.